New law or old issues: stakeholder expectations on the bill for the promotion of the elimination of Buraku discrimination. Issue 2 (2nd April 2020) - Bondy, Christopher
Abstract: In late 2016, the Japanese government implemented a new law addressing buraku issues: the Act for the Promotion of the Elimination of Buraku Discrimination (APEBD). How was it that this policy came to be, despite a nearly fifteen-year absence of laws directly engaging with buraku concerns? This article begins by examining the foundations that sparked the implementation of the APEBD. Next, it considers the Act's key components, highlighting both the strengths and weaknesses of the law. Following this, the article explores the perspectives of various stakeholders on the foundational elements of the Act. The stakeholders include the Buraku Liberation League (BLL, the largest social movement group for the burakumin), Buraku Heritage (a smaller organization made up of younger people), and lawmakers themselves. The article argues that while these actors all consider the law a good 'first step' there is more to be done. This article argues that although the law is an important step, it fits within a broader collection of Japanese laws known as 'principle laws' ( rinenhō ), whereby terminology is ambiguous, and foundations rest on administrative guidance and a lack of penalties.